Design, simulation and feasibility study of a combined CO2 mineralization and brackish water desalination process. (December 2019) - Oh, Jaewoo; Jung, Dabin; Oh, Seung Hwan; Roh, Kosan; Ga, Seongbin; Lee, Jay H.
Highlights: Integration between CO2 mineralization and desalination. Integrated process is designed and simulated. Economic viability and CO2 reduction potential are examined. Using wind-based electricity significantly improves the process performance. Abstract: This study presents a novel process integration scheme between CO2 mineralization and brackish water reverse osmosis (BWRO). The integration is based on the reciprocal nature of these two processes: While CO2 mineralization needs metal ions such as Na + to convert CO2 into mineral carbonates like sodium bicarbonate, BWRO is designed to reject such ions to produce fresh water. Thus, there is a potential synergy that can be gained through their integration. To examine the feasibility of such process integration, techno-economic analysis (TEA) and CO2 life cycle assessment (LCA) are conducted for various possible configurations of the integrated process. A key requirement for TEA and CO2 LCA is the availability of mass and energy balance data. Therefore, the process is simulated with the commercial simulation software tool of Aspen Plus combined MATLAB . Another requirement is the selection of appropriate evaluation scenarios. Based on a market analysis, the proposed process is assumed to be installed either in the US or in the China to replace a respective conventional benchmark process. Also, two sources of electricity (coal and wind onshore) are considered in the evaluation in order to investigate the sensitivity of the process performance on the type of electricity used. As a result of the analysis, the CO2 avoidance cost of the designed process is calculated to be 132˜245$/metric ton of CO2 with wind-based electricity. Given other advantages of the mineralization over the geological storage, the presented process integration between CO2 mineralization and BWRO deserves further investigation as a means to produce useful chemicals and fresh water while curbing CO2 emission.